A Summary and Update of Developing Annuities Markets : The Experience of Chile - Rocha, Roberto; Rudolph, Heinz P. (2012)
The rapid growth of the market for retirement products in Chile has its origins in the pension reform that was implemented in 1981. But the successful development of an active annuity market also reflects many other factors. This paper summarizes and updates an earlier longer study on the development of the Chilean annuity market. The update focuses on the numerous changes that were introduced in 2008. The most striking aspect of the Chilean experience is the very high rate of annuitization. This has been linked to the restrictions that have been applied to lump-sum withdrawals, the offer of inflation-protected annuities, and the robust prudential regulation of providers. But the level of annuitization has also been supported by the annuitization incentives provided to early retirees and the influence of brokers and sales agents. The recent regulatory changes have weakened the impact of the last two factors, while strengthening the demand for annuities at normal retirement.